Initial Preference for Labor Without Neuraxial Analgesia and Actual Use: Results from a National Survey in France. Issue 3 (September 2016) - Kpéa, L.; Bonnet, M.; Ray, C.; Prunet, C.; Ducloy-Bouthors, A.; Blondel, B.
Abstract : ( Anesth Analg . 2015;121:759–766) Neuraxial analgesia is an effective labor pain relief option for pregnant women. It can refer to epidural, spinal, or combined spinal-epidural analgesia. In principle, neuraxial analgesia use should be the women's choice. However, few studies have examined the association between women's initial preferences for this pain relief option and its actual administration. In this study, authors studied factors associated with a woman's preference to decline neuraxial analgesia, as well as the factors associated with the woman receiving neuraxial analgesia when she initially did not prefer it. Data were collected from a cross-section of the French 2010 National Perinatal Survey, which surveyed analgesia preference and provided information from medical records, interviews of women about their social/demographic characteristics, prenatal care, and pain management during labor, and questionnaires about maternity unit organization (535 maternity wards). Both univariate and multivariate analyses were conducted.